A perspective for resolving the systematics of Rattus, the vertebrates with the most influence on human welfare - Thomson, Vicki; Wiewel, Andrew; Chinen, Aldo; Maryanto, Ibnu; Sinaga, M. H.; How, Ric; Aplin, Ken; Suzuki, Hitoshi (Zootaxa, 2018)
The murid rodent genus Rattus Fischer 1803 contains several species that are responsible for massive loss of crops and food, extinction of other species and the spread of zoonotic diseases to humans, as well as a laboratory species used to answer important questions in physiology, immunology, pharmacology, toxicology, nutrition, behaviour and learning. Despite the well-known significant impacts of Rattus, a definitive evolutionary based systematic framework for the genus is not yet available. The past 75 years have seen more dramatic changes in membership of Rattus than in almost any other genus of mammals. In fact, the Rattus genus has been a receptacle for any generalised Old World murine that lacked morphological specialisation and at one point, has included more than 560 species and/or subspecies, spread across Eurasia, Africa and the Australo-Papuan region. The dissolution of Rattus is ongoing as many of its constituent species and many genera of Rattini remain unsampled in any molecular study. To address this sampling limitation, we sequenced the mitochondrial cytochrome b (cytb) gene and examined phylogenetic relationships using both Bayesian and Maximum Likelihood algorithms for an expanded set of taxa within Rattus and among closely related genera. Here we place previously unsampled taxa in a phylogenetic context for the first time, including R. burrus, R. hoogerwerfi, R. lugens, and R. mindorensis within the Asian Rattus group, R. facetus within the Australo-Papuan Rattus radiation, and the undescribed ‘Bisa Rat’ described by Flannery as sister to the recently described genus Halmaheramys. We also present an exploratory foray into the wider topic of Rattus phylogenetics and propose that a reorganisation of the Rattus genus should require that it be a monophyletic group, include at least the type species R. norvegicus and R. rattus (plus their close allies); and exclude the Bandicota/Nesokia clade and other such specialised genera.